Medicinal Plants for Rich People vs. Medicinal Plants for Poor People: A Case Study from the Peruvian Andes - Corroto, Fernando; Rascon, Jesús; Barboza Castillo, Elgar; Macía, Manuel J. (MDPI, 2022)
Traditional knowledge (TK) of medicinal plants in cities has been poorly studied across different inhabitants’ socioeconomic sectors. We studied the small city of Chachapoyas (~34,000 inhabitants) in the northern Peruvian Andes. We divided the city into three areas according to the socio-economic characteristics of its inhabitants: city center (high), intermediate area (medium), and city periphery (low). We gathered information with 450 participants through semi-structured interviews. Participants of the city periphery showed a higher TK of medicinal plants than participants of the intermediate area, and the latter showed a higher TK than participants of the city center. The acquisition of medicinal plants was mainly through their purchase in markets across the three areas, although it was particularly relevant in the city center (94%). Participants of all socioeconomic levels widely used the same medicinal plants for similar purposes in Chachapoyas, which is likely based on a common Andean culture that unites their TK. However, participants with the lowest socioeconomic level knew and used more plants for different medicinal uses, indicating the necessity of these plants for their livelihoods. City markets with specialized stores that commercialize medicinal plants are key to preserve the good health of poor and rich people living in Andean cities and societies.